Analysis of the corporate political activity of major food industry actors in Fiji. Issue 1 (December 2016) - Mialon, Melissa; Swinburn, Boyd; Wate, Jillian; Tukana, Isimeli; Sacks, Gary
Abstract Background Non-communicable diseases (NCDs) are the leading cause of mortality in Fiji, a middle-income country in the Pacific. Some food products processed sold and marketed by the food industry are major contributors to the NCD epidemic, and the food industry is widely identified as having strong economic and political power. However, little research has been undertaken on the attempts by the food industry to influence public health-related policies and programs in its favour. The "corporate political activity" (CPA) of the food industry includes six strategies (information and messaging; financial incentives; constituency building; legal strategies; policy substitution; opposition fragmentation and destabilisation). For this study, we aimed to gain a detailed understanding of the CPA strategies and practices of major food industry actors in Fiji, interpreted through a public health lens. Methods and results We implemented a systematic approach to monitor the CPA of the food industry in Fiji for three months. It consisted of document analysis of relevant publicly available information. In parallel, we conducted semi-structured interviews with 10 stakeholders involved in diet- and/or public health-related issues in Fiji. Both components of the study were thematically analysed. We found evidence that the food industry adopted a diverse range of strategies in an attempt to influence public policy in Fiji, with all six CPA strategies identified. Participants identified that there is a substantial risk that the widespread CPA of the food industry could undermine efforts to address NCDs in Fiji. Conclusions Despite limited public disclosure of information, such as data related to food industry donations to political parties and lobbying, we were able to identify many CPA practices used by the food industry in Fiji. Greater transparency from the food industry and the government would help strengthen efforts to increase their accountability and support NCD prevention. In other low- and middle-income countries, it is likely that a systematic document analysis approach would also need to be supplemented with key informant interviews to gain insight into this important influence on NCD prevention.